Optimization Of Laser Soldering Parameters On Passive Devices - Ahmad Nadzri, Faiz Farhan (Universiti Sains Malaysia, 2022)
Laser soldering is a non-contact process that is important in soldering technology for miniature components because it can emit a controlled heating from laser beam to a specific location of solder joint and this process also can prevent damaging other components on electronic devices. The process parameter of laser soldering also important to be known which is laser power, process time and shape of laser beam to produce a consistent soldering result. However, in this research study will focus on VOF model in ANSYS Fluent software and Steady State Heating in ANSYS Mechanical because the process parameter of laser soldering has been given by Western Digital. The main goal of this study is to optimize the parameters that affect the effectiveness in laser soldering process on passive devices. The parameter which is laser beam distance and solder type can affect the formation of fillet shape, velocity, and pressure of solder. Also, the effects of heat radiation from the laser beam are studied. Numerical simulation has been conducted to identify the suitable laser beam distance and the selection of solder type that can affect in solder joint reliability such as void formation. Thus, the parameters in the soldering process needed to be controlled to produce a good quality, long lifespan, and more reliable solder joint. The results obtained from the simulation can be visualise the flow of solder at the end of reflow process in contour of volume fraction and temperature. The visualisation results can show the details trajectory of solder as it undergoes the thermal reflow. Besides, good relation can be seen between the simulation results obtain and validation from IPC standard. The study of VOF model showed the usable of simulation approach to simulate the process of laser soldering that can produce a good results of solder joint.